ORAL APPLIANCES USED FOR OBSTRUCTIVE SLEEP APNEA: A review - Manohar, Janhvi; Ganapathy, Dhanraj; Kumar Pandurangan, Kiran; Velayudhan, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Obstructive sleep apnea is a sleep disorder in which a person stops breathing periodically throughout the night due to physical obstructions of the airway, with a predilection among middle-aged males. Oral appliances are devices that can be used to treat mild or moderate obstructive sleep apnea, as well as snoring. The treatment of OSA depends on the severity of symptoms, magnitude of clinical complications, and etiology of upper airway obstruction. It can be treated by lifestyle modifications, CPAP (continuous positive airway pressure), surgery, or oral appliances. Oral appliances, which are of recent development, work by positioning the mandible in a protruded position during sleep. Oral appliances are of several types: Mandibular Advancement Splints (MAS), Mandibular Advancement Devices (MAD), Mandibular Repositioning Appliances (MRA), or Tongue Retaining Devices (TRD), which hold your tongue in place to keep your airway open while asleep, and Adjustable Soft Palate Lifters. The comparison between oral appliances of different designs and the literature of sleep apnea provides better evidence for the efficacy of this treatment modality and thus more scope for its development. The aim of this article is to review literature regarding the various types of oral appliances in the treatment of sleep apnea syndrome, their mechanism of action, factors affecting their performance, complications, and patient compliance.